Hubungan antara Stres Akademik dan Prokrastinasi Akademik dengan Prestasi Belajar Siswa Kelas X Sekolah Menengah Atas - Lia Artika Sari; Djoko Budi Santoso; Ella Faridati Zen (Universitas Negeri Malang, 2022)
Abstract: The purpose of this study is to determine the relationship between academic stress and academic procrastination with learning achievement. This study used a correlational research design. The population of this research was the X graders of SMA Brawijaya Smart School Malang with a total of 194 students, the research sample totaling 100 students obtained using the Slovin formula with an error tolerance of 7 percent. The sampling using simple random sampling method. This study used research instrument in the form of scales. First,